The Effect of Vat (Vat) and Payroll Tax(Pph21) on the Growth of Community Consumption, Gross Domestic Product, and Economic Growth in Indonesia - Rio Johan Putra; Shiva Dewanti Nabila (Journal Research of Social Science, Economics, and Management, 2022)
Taxes play an important role in the existence of the state, especially in implementing improvements, considering that income from the expenditure sector can fund the development of national consumption. This study aims to determine the effect of VAT (VAT) and PPH (payroll tax) on the growth rate of public consumption, gross domestic product and the rate of economic growth in Indonesia as a moderating variable in country data in the statistical center and databox starting from 2002 - 2021. This sample uses country data for 20 years, This study uses multiple linear regression assisted by SPSS version 24 program. The results of this study shows that PPN and PPH affect the level of public consumption, while PPN and PPH have no effect on Gross Domestic Product and also Indonesia's Economic Growth Rate. That is, it can be concluded that VAT has no effect on the level of economic development in Indonesia which is registered in the Central Statistics Agency and the database for the period 2002 – 2021. Thus, the hypothesis is rejected.